2014
DOI: 10.1103/physrevlett.113.137602
|View full text |Cite
|
Sign up to set email alerts
|

Orbital-Ordering-Driven Multiferroicity and Magnetoelectric Coupling inGeV4S8

Abstract: We report here the discovery of multiferroicity and large magnetoelectric coupling in the type I orbital order system GeV₄S₈. Our study demonstrates that this clustered compound displays a para-ferroelectric transition at 32 K. This transition originates from an orbital ordering which reorganizes the charge within the transition metal clusters. Below the antiferromagnetic transition at 17 K, the application of a magnetic field significantly affects the ferroelectric polarization, revealing thus a large magneto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(114 citation statements)
references
References 39 publications
16
98
0
Order By: Relevance
“…The 17 K AFM transition appears as a cusp in the susceptibility curve. The observed Néel temperature is consistent with previous reports that have ranged from 13 to 18 K. 7,15,16 The step-like transition observed at 31.5 K has been shown to be the consequence of a structural transition from cubic (possibly tetragonal, as noted above) to orthorhombic. 16 Above the structural transition at 31.5 K, the inverse susceptibilities are studied to discuss the Curie-Weiss behavior.…”
Section: Experimental Methodssupporting
confidence: 91%
“…The 17 K AFM transition appears as a cusp in the susceptibility curve. The observed Néel temperature is consistent with previous reports that have ranged from 13 to 18 K. 7,15,16 The step-like transition observed at 31.5 K has been shown to be the consequence of a structural transition from cubic (possibly tetragonal, as noted above) to orthorhombic. 16 Above the structural transition at 31.5 K, the inverse susceptibilities are studied to discuss the Curie-Weiss behavior.…”
Section: Experimental Methodssupporting
confidence: 91%
“…Orbital excitations were found to be the key in understanding the temperature dependence of the resistivity and optical conductivity in the ferromagnetic phase of doped manganites [4]. The multiferroicity in GeV4S8 is thought to originate from an orbital ordering that reorganizes the charge within the transition metal clusters [5]. Furthermore, electron orbitals are considered to be the origin of the extremely anisotropic superconducting gap in the nematic phase of FeSe superconductors [6].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the cubane-like metallic clusters are characterized by an only partly filled electronic shell and, hence, most of the lacunar spinels are Jahn-Teller active [8]. Recently, for GeV4S8 [9] and GaV4S8 [10] it has been shown that the onset of orbital order and the resulting Jahn-Teller distortion induces ferroelectricity, and, thus, these compounds are multiferroic. The polar dynamics in GaV4S8 at the phase transition has been probed by dielectric and THz spectroscopy [11].…”
Section: Introductionmentioning
confidence: 99%